Induced defense strategies of plants against Ralstonia solanacearum - Shi, Haoqi; Liu, Yong; Ding, Anming; Wang, Weifeng; Sun, Yuhe (Frontiers in Microbiology, 2023)
Plants respond to Ralstonia solanacearum infestation through two layers of immune system (PTI and ETI). This process involves the production of plant-induced resistance. Strategies for inducing resistance in plants include the formation of tylose, gels and callose and changes in the content of cell wall components such as cellulose, hemicellulose, pectin, lignin and suberin in response to pathogen infestation. When R. solanacearum secrete cell wall degrading enzymes, plants also sense the status of cell wall fragments through the cell wall integrity (CWI) system, which activates deep-seated defence responses. In addition, plants also fight against R. solanacearum infestation by regulating the distribution of metabolic networks to increase the production of resistant metabolites and reduce the production of metabolites that are easily exploited by R. solanacearum. In the review, we review the strategies used by plants to induce resistance in response to R. solanacearum infestation. In particular, we highlight the importance of plant-induced physical and chemical defences as well as cell wall defences in the fight against R. solanacearum.